2012
DOI: 10.1007/8904_2012_182
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Novel Mutations of Lysosomal Storage Disorders in United Arab Emirates

Abstract: Lysosomal storage disorders (LSD) are rare entities of recessive inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 21 publications
(13 reference statements)
3
43
0
Order By: Relevance
“…This is also supported by recent reports on late‐onset forms of Krabbe disease . The overall live birth prevalence of LSDs in several countries has been reported during the last 15 years , with figures ranging from 7.6 to 26.9 per 100 000 live births.…”
Section: Introductionsupporting
confidence: 75%
“…This is also supported by recent reports on late‐onset forms of Krabbe disease . The overall live birth prevalence of LSDs in several countries has been reported during the last 15 years , with figures ranging from 7.6 to 26.9 per 100 000 live births.…”
Section: Introductionsupporting
confidence: 75%
“…Recent decades have witnessed a burgeoning of clinical interest in understanding the genetic basis of disease . Genetic diseases, such as hemoglobin disorders, inherited metabolic diseases, neuro-genetic disorders and birth defects, are common among Arab populations, particularly in the United Arab Emirates, likely as a result of the relatively high rate of consanguineous marriages (Tadmouri et al 2009;Bayoumi and Yardumian 2006;Al-Gazali and Ali 2010;Al-Jasmi et al 2013). The high prevalence of non-communicable diseases in the population has also led to an increase in genetic research studies in an effort to identify specific mutations and genetic aberrations (Al-Gazali and Ali 2010).…”
mentioning
confidence: 99%
“…Twenty out of 40 key opinion leaders (KOL) and patient organisations (POR) responded to our communications (50%) of which 9 provided data (23%). Two KOL’s provided additional data not included in their publications [ 25 , 26 ]. Analysis of the included data indicated that 4 KOL and 11 published studies provided data for cases or prenatal diagnoses which could not be used to calculate prevalence and were excluded (summarised in Additional file 4 ).…”
Section: Resultsmentioning
confidence: 99%